Comparison of surgically induced astigmatism after superotemporal and superonasal clear corneal incisions in post phacoemulsification - Md Mustafa, Md Muziman Syah; Marzuki, Nazaryna; Mohd. Kamal, Khairidzan; Ab Halim, Noorhazayti (2018)
Objective: To compare the surgically induced astigmatism (SIA) of 2.75mm superotemporal and superonasal clear corneal incisions in post phacoemulsification.